Analysis Of Marketing Strategies In Small To Medium Printing Enterprise (Case Study Of Printing Sme The Bejos Screen Printing, Palopo City, South Sulawesi - Dian Nirmasari; Munawarah; Adelia Dwi Putri (International Journal of Management and Business Economics, 2024)
Marketing Strategy Analysis in Small and Medium Enterprises Printing (Case Study of Printing UKM The Bejos Screen Printing Palopo City, South Sulawesi), Thesis Management Study Program Faculty of Economics and Business, University of Muhammadiyah Makassar. Printing The Bejos Screen Printing is one of the SMEs located in Palopo City, South Sulawesi, which has been developing since 2013, The Bejos Screen Printing printing has been printing clothes. Since starting its printing business, The Bejos Screen Printing has always been faced with various obstacles and obstacles, many similar companies that appeared to make Printing The Bejos Screen Printing difficult to maintain the position of its products due to increasingly fierce industry competition. The condition of intense competition is a problem faced by The Bejos Screen Printing. The purpose of this study was to determine the marketing strategy of printing SMEs through a SWOT analysis. In determining the marketing strategy, it is necessary to know the internal factors of strengths and weaknesses, external factors of opportunities and threats. The strategy that can be applied is the ST Strategy is a strategy that uses the strength of the company to overcome threats or commonly called diversification strategies.